Front-line daratumumab-VTd versus standard-of-care in ASCT-eligible multiple myeloma: matching-adjusted indirect comparison - Moreau, Philippe; Hebraud, Benjamin; Facon, Thierry; Leleu, Xavier; Hulin, Cyrille; Hashim, Mahmoud; Hu, Yannan; Caillot, Denis; Benboubker, Lofti; Zweegman, Sonja; Merz, Maximilian; Weisel, Katja; et al. (Immunotherapy, 2021)
Aim: To compare daratumumab plus standard-of-care (SoC; bortezomib/thalidomide/dexamethasone [VTd]) and VTd alone with other SoC for transplant-eligible newly diagnosed multiple myeloma. Patients & methods: We conducted an unanchored matching-adjusted indirect comparison of progression-free and overall survival (PFS/OS) with D-VTd/VTd versus bortezomib/lenalidomide/dexamethasone (VRd), bortezomib/cyclophosphamide/dexamethasone (VCd) and bortezomib/dexamethasone (Vd). Results: After matching adjustment, significant improvements in PFS were estimated for D-VTd versus VRd (hazard ratio [HR]: 0.47 [95% CI: 0.33-0.69]), VCd (HR: 0.35 [95% CI: 0.21-0.58]) and Vd (HR: 0.42 [95% CI: 0.28-0.63]). OS was significantly longer with D-VTd versus VRd (HR: 0.31 [95% CI: 0.16-0.57]), VCd (HR: 0.35 [95% CI: 0.14-0.86]) and Vd (HR: 0.38 [95% CI: 0.18-0.77]). No significant PFS/OS differences were seen for VTd versus other SoC. Conclusion: This analysis supports front-line daratumumab for transplant-eligible newly diagnosed multiple myeloma.